Cathodic Corrosion Protection on Low Carbon Steel Type H-beam (SM490YB) Using Zinc (Zn) Anode with Soil Corrosive Media Mixed with NaCl - Lazuardi, Lazuardi; Rizza, Muhammad Akhlis; Hadi Susilo, Sugeng; Maryono, Maryono (CV. Creative Tugu Pena, 2023)
H-beam steel is often used as a basic material for building construction on the coast. Cases that often occur are H-beam steel that is installed quickly corrodes. This incident is caused by the coastal area belongs to an environment with a high level of corrosiveness.From the results of the pH tester test, the value of the degree of acidity is in rangeof pH=5 to pH=7.Coastal soils contain a lot of chloride Cl. In an acidic environment accompanied by a chloride Cl element, it triggers the breakdown of the passive layer on the surface which causes an anodic region to form so that the steel is in a state of releasing electrons. The problem that occurs can be overcome using a sacrificial anode cathodic protection system, with a zinc metal protection mechanism (Zn) 99, 99% which is used as a sacrificial anode has a lower potential value than the potential value of H-beam steel as a cathode protected by zinc metal (Zn) . This value of zinc metal (Zn) is more negative than the Fe steel which potential value is . The value of the potential difference is that it can be ascertained that the released Zn electrons can flow and adhere to the protected H-beam steel. Keywords: Surface Corrosion, Cathodic Protection, H-beam Steel, Zinc Anode(Zn)